In-field evaluation of a managed IP and MPLS over WDM provisioning solution. - Karayannis, Fatis
This article demonstrates results and experiences gained in the area of multilayer internetworking, with emphasis on bandwidth on-demand provisioning as well as resource and restoration management. Behavioral characteristics and numerical results were obtained from a management. system prototype implemented and tested in an appropriately adapted commercial WDM environment enhanced with multivendor gigabit IP routers. The management solution, the testbed environment, and a representative evaluation scenario are presented as a means of explaining in detail the results that finally allow a global system assessment.
Keywords: WDM provisioning solution; bandwidth on-demand provisioning; managed IP-MPLS.; multilayer internetworking; multivendor Gigabit IP routers; restoration management